Joan of Arc : [photographic story of a life] - Kudlinski, Kathleen V. (New York : DK Pub., 2008)
A look at the young peasant woman who led the French army to victory over the English and saw the crowning of the French king, and later was made a saint.
Includes bibliographical references (p. 124-125) and index.
BIO mc
Keywords: Joan, -- of Arc, Saint, -- 1412-1431 -- Juvenile literature; Christian women saints -- France -- Biography -- Juvenile literature; Hundred Years' War, 1339-1453 -- Juvenile literature; Saints -- Juvenile literature; France -- History -- Charles VII, 1422-1461 -- Juvenile literature; Biography, Juvenile